EFEKTIVITAS UNDANG-UNDANG PERKAWINAN DALAM MENANGANI GUGATAN CERAI KARENA PENGABAIAN NAFKAH: ANALISIS NORMATIF YURIDIS TERHADAP AKSES KEADILAN BAGI PEREMPUAN - Atmojo, Talitha Maheswari Ning; Sidi Ahyar Wiraguna (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Economic factors are one of the dominant causes behind the rising divorce rate in Indonesia. Economic instability, unemployment, and social inequality are the main triggers that lead to a husband’s inability to fulfill his financial obligations to his wife and children. This study aims to analyze the effectiveness of Law Number 1 of 1974 concerning Marriage in providing a legal basis for divorce due to neglect of financial support, which occurs when a husband fails to provide for his family for two consecutive years. The research method used is normative juridical with a qualitative approach, involving an analysis of statutory regulations, legal literature, and religious court decisions. The results indicate that the implementation of this provision faces significant obstacles, including difficulties in proving neglect, limited access to justice for impoverished women, and formal requirements that do not align with social realities. Therefore, a reform of family law is needed to be more responsive to the principles of substantive justice, particularly in protecting the economic rights of women and children.